Mid-Term Clinical and Echocardiographic Outcomes of Percutaneous Transvenous Mitral Commissurotomy in Patients with Rheumatic Mitral Stenosis - Muhammad Ijaz Khan, Muhammad Omer Hashmi, Subtain Ul Hassan Abid, Bahauddin Khan, Hamid Iqbal, Fahmida Khatoon (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Mitral stenosis is a condition characterized by the narrowing of the mitral valve, which regulates blood flow between the left atrium and left ventricle of the heart. Objectives: The main objective of the study is to find the mid-term clinical and echocardiographic outcomes of percutaneous transvenous mitral commissurotomy in patients with rheumatic mitral stenosis. Material and Methods: The present study was a retrospective observational study conducted at Ayub Teaching Hospital, Abbottabad. The study included a total of 70 patients who underwent percutaneous transvenous mitral commissurotomy (PTMC) between 1st January 2022 and 30th June 2022. Results: A total of 70 patients who underwent PTMC at Ayub Teaching Hospital, Abbottabad, between 1st January 2022 and 30th June 2022 were included in this retrospective observational study. The mean age of the patients was 39.2 ± 12.8 years, and 52 (74.3%) were females. The mean mitral valve area (MVA) prior to PTMC was 0.9 ± 0.2 cm^2 that increased to 1.8 ± 0.3 cm^2 after the procedure, and it was statistically significant (p<0.001). The immediate success rate of PTMC was 94.3%, while the mid-term success rate was 90%. Conclusion: In conclusion, percutaneous transvenous mitral commissurotomy (PTMC) is a safe and effective treatment option for patients with rheumatic mitral stenosis. Our study showed that PTMC resulted in a significant improvement in mitral valve area, trans-mitral pressure gradient, pulmonary artery systolic pressure, and clinical symptoms of dyspnea, fatigue, and palpitations. Keywords: Mitral stenosis, PTMC, Patients, Procedures, MVA